A novel approach toward the multigram synthesis of a novel Bcl2-specific inhibitor, and evaluation of its biological activity - Manthra Raveendran; Shivangi Sharma; Sanjay Sambhajirao Palimkar; M. Lakshmana Kumar; H. Sahana; Hassan A. Swarup; Sathees C. Raghavan (Elsevier, 2024)
The antiapoptotic protein BCL2 is overexpressed in several cancers. It contributes to prolonged cell survival and chemoresistance, making it an excellent target for targeted cancer therapy. Over the years, several BCL2 inhibitors have been investigated extensively for their anticancer potential; however, most of them were abolished before clinical use due to their pan activity. There is only one FDA-approved BCL2-specific inhibitor, Venetoclax, currently used in clinics. Previously, we reported the characterization and development of a novel BCL2 inhibitor, Disarib, which is selective against BCL2 and predominantly binds to the BH1 domain of BCL2. Importantly, the efficacy of Disarib was equally good or better than Venetoclax in various in vitro and in vivo assays. In the present study, we report the development of a scalable and practical method for the large-scale synthesis of Disarib to support the ongoing pre-clinical studies. The parameters of each step were optimized through prior knowledge, helping in improving the yield and purity to 98.8 %. Further, we compared the efficiency of a large-scale synthesized Disarib in a GLP-certified laboratory with that of an in-house synthesized Disarib. The results showed that the biological activity, including Disarib-induced cytotoxicity and cell cycle progression, were comparable. Besides, the tumor regression efficacy and pharmacokinetics analysis of Disarib have shown comparable results when Disarib synthesized in both routes were tested. Thus, a robust and scalable synthetic pathway of Disarib has developed to address small-scale synthesis's limitations in supporting their expanded applications and use.